Nutritional status and quality of life of patients after pacemaker implantation - Kamil Sikora; Agnieszka Wawryniuk; Robert Jan Łuczyk; Marta Łuczyk (Kazimierz Wielki University, 2021)
Introduction. Nutritional status is one of the factors determining the quality of life of patients. However, there are few reports on the correlation between nutritional status and quality of life in the group of patients with implanted cardiac pacing system. Purpose of research. The aim of the study was to assess the impact of nutritional status on the quality of life of patients with implanted pacemakers. Material and methods. 100 patients after pacemaker implantation, hospitalized at the cardiology clinic and treated at the SPSK 4 cardiology clinic in Lublin were examined. Standardized research tools were used - the WHOQOL-Bref questionnaire to assess the quality of life and the shortened scale to assess the nutritional status (MNA-SF). The results of the obtained research are summarized in the statistical analysis. Results. The average result of the respondents obtained in the MNA scale was 11.86 points with a standard deviation of 2.26. The nutritional status of the most of respondents (61%) was normal. In the studied group 35% were at risk of malnutrition, while 4% were malnourished. Statistically significant relationships between the nutritional status and quality of life were demonstrated in all domains. If the nutritional status of the respondents was better, their overall quality of life was higher, as well as their self-assessment of health. Conclusions. The overall assessment of the nutritional status of the studied patients is within the normal ranges. Nutritional status has an impact on the quality of life of respondents after pacemaker implantation in all QoL domains. High quality of life conform to the correct assessment of the nutritional status in the most of the studied patients.